Physical Demarcation of Infrastructures and Making Detailed Physical Planning of Kabeza Site - Jean Pierre Habiyaremye, (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Physical infrastructure is the basic physical structures required for an economy to function and survive. Rwanda, like other developing countries, its plans focus on the contribution to the solutions of the problems arising due to lack of well-planned local urban upgrading. The infrastructures that allow the access to the services of the population within the country must be maintained, constructed for better achievement of different goals at different levels from the Central Government up to the Sector level. This paper therefore examined the demarcation of the infrastructures and the detailed physical planning as a key component of urban development initiatives. The physical planning sets the boundaries with the purpose of having access to affordable infrastructure services for consumption purposes serves to improve household welfare and affordable housing and promoting a sustainable development for the benefit of the individual, for society and for future generation. The project was conducted in Kabeza Site, Eastern Province, Bugesera District, Ntarama Sector, Kanzenze Cell and Kabeza Village in Republic of Rwanda. Experimental and survey design have used in the assessment of existing physical features around and within the site by observation method using DGNSS Receivers, total stations, and also used participatory approach method. The study involved a detailed topographic survey of existing features on Kabeza site. An interview of stakeholders was conducted during the community meeting. Different software were used to analyze and re-plotting the physical planning. Findings show that the rapid rate of urbanization has led to a rise in informal settlements facing with the problems including lack of sufficient and adequate basic infrastructures. The paper therefore canvassed for immediate evolvement of physical plan that emphasis on keeping commitment to place, establishing the quality recreation areas and diversifying housing options. It was revealed that there is a need to establish a well planned roads, create a more vibrate village centre, light the whole village, establish a water system in the whole village, maintain and upgrade the greening village infrastructures, build community from assessment of the existing land use land cover, make and re-plot the new parcels within the site and to design details physical layout plan of that region. The study recommends the project implementers and partners, particularly the local government units overseeing the project site, to pay attention to the growing income disparity and the exclusion of the poorest from development process. Government should identify measures to minimize the interventions that impact negatively the life of well-being of the poor and women and also to minimize negative impacts on the environment.